Outcomes of Mechanical Thrombectomy in Patients With Ischemic Stroke and Heart Failure. A Systematic Review and Meta‐analysis - D'Anna, Lucio; Bax, Francesco; Valente, Mariarosaria; Sacco, Simona; Foschi, Matteo; Ornello, Raffaele; Kanagaratnam, Prapa; Lim, Boon; Simister, Robert; Zhang, Liqun; Nguyen, Thanh N.; Veltkamp, Roland; et al. (Stroke: vascular and interventional neurology, 2025)
BackgroundPatients with heart failure (HF) treated with mechanical thrombectomy (MT) for acute ischemic stroke were underrepresented in clinical trials on MT. Our systematic review and meta‐analysis aim to assess differences in outcomes between patients with HF and their counterparts without HF treated with MT for acute ischemic stroke.MethodsA systematic review of the English language literature from inception up to March 7, 2024, was conducted using PubMed, Embase, Cochrane Library, and Web of Science databases. Studies focused on patients with and without HF who were treated with MT for acute ischemic stroke were included. The primary outcome of interest was the rate of modified Rankin Scale scores of 0–2 at 90 days. Secondary outcomes of interest included rates of 90‐day mortality, successful reperfusion, and symptomatic intracranial hemorrhage.ResultsOf 5394 initially retrieved studies, 5 studies were included in the systematic review with a final population of 44 385 patients with ischemic stroke with and without HF treated with MT. Four studies were combined for the primary outcome and showed comparable rates of 0–2 modified Rankin Scale scores between patients with HF and patients without HF (odds ratio, 0.86 [95% CIs, 0.70–1.06]; P = 0.15). Ninety‐day mortality was significantly higher in the HF group (odds ratio, 1.92 [95% CIs, 1.66–2.23]; P<0.0001) although the sample size was small (n of study = 3) and only unadjusted estimates were used. Successful reperfusion and symptomatic intracranial hemorrhage rates were similar between the groups.ConclusionIn this systematic review and meta‐analysis, patients with HF experienced worse 90‐day mortality post‐MT. Our data encourage further research on MT outcomes in patients with large vessel‐occlusion ischemic stroke and concomitant HF.